Transnational Led Privatisation and the New Regime for the Global Governance of Water - Varghese, Shiney (Water Nepal, 2003)
Many aspects of the current and looming freshwater crisis can be traced to the basis on which water resource development and management is organised. In this context, it is necessary to formulate a socially just and environmentally sustainable approach to water issues. This paper, outlines four components of such an approach. First, this paper emphasises the need for recognising water as a fundamental human right and explore what is at stake in that recognition. Second, it stresses the limits and dangers of the current approach centered on privatisation of water, which assumes that water is only an economic good. As an alternative, this paper explores the potentialities of recognising that water is foremost a social good and only then an economic good. Third, it outlines areas where structural changes in patterns of water use have to come about. The two primary areas of focus are pollution and consumption. Finally it explores the global governance issues involved in this alternative strategy. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.77-105